Delayed Posttraumatic Tension Pneumocephalus: A Rare Case Report and Review of the Literature - Tawfiq Abdulmohsen Almezeiny; Mody Abdulrahman Almarshad (Dr. Sulaiman Al Habib Medical Journal)
Pneumocephalus (PNC) is defined as a pathological air collection inside the skull in the epidural, subdural, subarachnoid, intraventricular, or intraparenchymal compartments. The rate at which the air accumulates inside the cranium could be acute (<72 h) or delayed (≥72 h). Tension PNC (TP) occurs when the air collection exerts an abnormally high pressure on the brain, compared with the pressure outside the cranium, resulting in a mass effect and neurological symptoms. PNC, also called pneumocranium, can be spontaneous or acquired. Trauma remains the most common cause of acquired PNC. A 34-year-old gentleman presented with a short duration history of sudden severe headache, vomiting, and clear fluid leak from the left nostril. He had history of trauma, which occurred 3 months ago. Computed Axial Tomography (CAT) scan revealed intra-axial and extra-axial PNC plus an old depressed fracture of the left side of the frontal bone. Eventually, he was scheduled for surgical bifrontal craniotomy, repair of posterior sinus fracture, and recanalization of frontal sinus. Delayed TP is a rarely occurring pathology, and in rare cases it can occur many weeks after trauma. It is a life-threatening neurosurgical emergency that needs to be managed on urgent basis. Based on the literature review and the success achieved in this case, early surgical management is the optimal treatment for TP.